Seasonal histological changes and aquaporin 5 immunoreactivity in the ductus deferens and prostate gland of Saudi Arabian dromedary camel. (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: The present study aims to investigate the seasonal histological structure changes and immunoreactivity of Aquaporin 5 (AQP-5) in the ductus deferens and prostate under the light microscope. Materials and Methods: For the present study, twelve mature male camels were employed. Following the animals breeding and non-breeding seasons of slaughter under official licensing and veterinary supervision, samples were obtained from various regions of the ductus deferens and prostate gland and processed using general histology and immunohistochemical methods. Results: The secretory end pieces of the vas deferens ampulla and prostate gland of the Saudi Arabian dromedary camel were well developed during reproductive and non-reproductive seasons. The spermatozoa were noticed in the lumen of the ductus deferens during the reproductive and non-reproductive seasons. The response of AQP-5 in the ductus deferens was particularly significant throughout the not-rutting season. Moreover, during the non-breeding season, the prostate gland showed a strong to moderate response. In the breeding season, the ampulla of the ductus deferens showed an insignificant reaction. Additionally, the body and disseminated portion of the prostate gland showed a mild to moderate response. Conclusion: The results suggested that Saudi Arabian dromedary camels might produce sperm during rutting and non-rutting seasons.J. Adv. Vet. Anim. Res., 11(3): 703–710, September 2024http://doi.org/10.5455/javar.2024.k820